Nanostructured system based on hydroxyapatite and curcumin: A promising candidate for osteosarcoma therapy. Issue 12 (15th June 2023) - Marinho, Jéssica Pauline Nunes; Neme, Natalia Paz; Matos, Matheus Josue de Souza; Batista, Ronaldo Junio Campos; Macedo, Waldemar Augusto de Almeida; Gastelois, Pedro Lana; Gomes, Dawidson Assis; Rodrigues, Michele Angela; Cipreste, Marcelo Fernandes; Sousa, Edésia Martins Barros de
Abstract: Osteosarcoma is the most common type of bone cancer. Despite therapeutic progress, survival rates for metastatic cases or that do not respond well to chemotherapy remain in the 30% range. In this sense, the use of nanotechnology to develop targeted and more effective therapies is a promising tool in the fight against cancer. Nanostructured hydroxyapatite, due to its biocompatibility and the wide possibility of functionalization, is an interesting material to design nanoplatforms for targeted drug delivery. These platforms have the potential to enable the use of natural substances in the fight against cancer, such as curcumin. Curcumin is a polyphenol with promising properties in treating various types of cancer, including osteosarcoma. In this work, hydroxyapatite (n-HA) nanorods synthesized by the hydrothermal method were investigated as a carrier for curcumin. For this, first-principle calculations based on the Density Functional Theory (DFT) were performed, in which the modification of curcumin (CM) with the coupling agent (3-aminopropyl) triethoxysilane (APTES) was theoretically evaluated. Curcumin was incorporated in n-HA and the drug loading stability was evaluated by leaching test. Samples were characterized by a multi-techniques approach, including Fourier transform infrared spectroscopy (FTIR), UV–visible spectroscopy (UV–Vis), X-ray diffraction (XRD), X-ray fluorescence spectrometry (FRX), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), zeta potential analysis (ζ), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). The results show that n-HAs with a 90 nm average size were obtained and successful incorporation of curcumin in the nanostructure was achieved. Cell viability and the number of osteosarcoma cells were decreased by CMAP-HA treatment. Furthermore, the stability test suggests that hydroxyapatite nanoparticles present great potential for the transportation of curcumin in the bloodstream, crediting this system for biological performance evaluations aiming at the treatment of osteosarcomas. Keywords: nanostructures, curcumin, hydroxyapatite, osteosarcoma.